New Developments in Anxiety Disorders 2016
DOI: 10.5772/65188
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media on Social Anxiety: A Systematic Review

Abstract: Introduction: Online social networking sites are being used all around the world. However, only recently researchers have started to investigate their relationship with mental health. Evidence coming from literature suggests that they have both advantages and disadvantages for individuals. The aim of this study is to critically review the existent research conducted on the relationship between online social networking and social anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 45 publications
3
46
0
2
Order By: Relevance
“…Recent accounts suggest that levels of social anxiety may be rising. Studies have indicated that greater social media usage, increased digital connectivity and visibility, and more options for non-face-to-face communication are associated with higher levels of social anxiety [32][33][34][35]. The mechanism underpinning these associations remains unclear, though studies have suggested individuals with social anxiety favour the relative 'safety' of online interactions [32,36].…”
Section: Introductionmentioning
confidence: 99%
“…Recent accounts suggest that levels of social anxiety may be rising. Studies have indicated that greater social media usage, increased digital connectivity and visibility, and more options for non-face-to-face communication are associated with higher levels of social anxiety [32][33][34][35]. The mechanism underpinning these associations remains unclear, though studies have suggested individuals with social anxiety favour the relative 'safety' of online interactions [32,36].…”
Section: Introductionmentioning
confidence: 99%
“…According to which, socially skilled individuals use online social networking sites to find additional opportunities to interact with others. There is mixed evidence regarding the two hypotheses, as both have received support [72,73].…”
Section: Media and Social Anxiety Disordermentioning
confidence: 99%
“…Future research could therefore benefit from, for example, examining these a ssociations in aging populations. In the context of longitudinal studies, it is also worth noting that the focus on correlational studies, and dearth of experimental studies, means that we have limited grounds to establish mechanisms (Dobrean & Păsărelu, 2016).…”
Section: Replication Reflectionsmentioning
confidence: 99%
“…of those found such a relationship, although some of the reported relationships were positive whereas others were negative (Dobrean & Păsărelu, 2016). A meta-review of internet use more broadly concluded that social anxiety was not significantly correlated with time spent online overall (Prizant-Passal, Shechner, & Aderka, 2016).…”
Section: Introductionmentioning
confidence: 99%